SYNCHRONOUS & ASYNCHRONOUS LEARNING DALAM PERKULIAHAN FIKIH WUDU MASA PENDEMI COVID-19 DI UNAIC - Pambudi, Satriyo; Fauzi, Fauzi (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to describe Synchronous & Asynchronous Learning in wudu fiqh lectures at UNAIC (Universitas Al-Irsyad Cilacap). This type of research is a descriptive qualitative research. Data obtained through exploring unstructured. The results of the study indicate that Synchronous & Asynchronous Learning is very supportive in lecture activities, especially in Religion courses. Namely by using the Zoom Cloud Meeting media, the Yufid TV channel on Youtube, and the WhatsApp application. In addition, Synchronous & Asynchronous Learning in wudu fiqh lectures at Al-Irsyad University Cilacap students requires lecturers to be good at choosing the right media, lecturers must have creative and innovative ideas so that lectures can continue even in the situation and conditions of the Covid-19 pandemic that all limited.